Conversion therapy combined with ALPPS for the treatment of intrahepatic cholangiocarcinoma: a case report - Tian, Hengyu; He, Qinghua; Wan, Chidan (Frontiers in Oncology, 2025)
RationaleIntrahepatic cholangiocarcinoma (ICC) is a highly malignant liver tumor with limited treatment options for advanced cases. Conversion therapy combining immunotherapy, targeted therapy, and chemotherapy offers a promising approach to enable surgical resection, which remains the only curative option.Patient concernsA 67-year-old male presented with right upper abdominal pain for two months. Imaging and biopsy confirmed advanced ICC (Stage IV), with a 98 mm tumor, lymphadenopathy, and elevated tumor markers (CA199: 1190.4 U/ml). The disease was deemed unresectable.DiagnosisThe patient was diagnosed with advanced ICC involving a large hepatic mass, lymph node metastasis, and insufficient liver reserve for conventional resection.InterventionsThe patient received six months of oxaliplatin plus gemcitabine (GEMOX), lenvatinib, and toripalimab, achieving significant tumor regression. A two-step ALPPS procedure was then performed, comprising portal vein ligation and right hepatectomy.OutcomesThe treatment reduced tumor size (98 mm to 60 mm), normalized tumor markers, and improved liver reserve. Postoperative pathology confirmed >80% tumor remission with negative margins. At 12 months post-surgery, the patient remained disease-free.LessonsThis case demonstrates that advanced ICC can be downstaged with systemic therapy, enabling resection via ALPPS. The combination of GEMOX, lenvatinib, and toripalimab is an effective and safe conversion therapy regimen. This approach may serve as a model for managing similar advanced cases.